Coupling chemo-mechanical model for smart structured electrode with great mechanical long life and electrochemical performance. (15th December 2021) - Zhang, Yudong; Shi, Yutao; Weng, Li; Xu, Chengjun; Gao, Chaojie; Chen, Bingbing; Zhou, Jianqiu; Cai, Rui
Highlights: The coupling chemo-mechanical behavior of smart structured electrode is obtained. Smart structured design can provide more space for electrode lithiated expansion. Mechanical stress can affect electrode electrochemical performance greatly. Smart structured electrode has long life and great electrochemical performance. Abstract: In battery cyclic operation, the diffusion of lithium atoms and its induced electrochemical reactions can result in the huge mechanical stress and electrode volume expansion, which may influence the electrode stability and lead to the electrode polarization. The smart structured material in a shape of hollow re-entrant honeycomb is reported to have great mechanical fracture resistance and shows perfect mechanical property. In this paper, a new analytical model is developed to study the coupling chemo-mechanical behavior of the smart structured electrode in battery cyclic operation. Our study reveals the smart structured design can help to lower the electrode mechanical stress level, provide more space for electrode lithiated expansion and realize the mechanical long life of electrode. Furthermore, smart structured electrode can solve the inconformity problem of electrode potential to some degree. It may generate less overpotential and voltage gap than thin film electrode in cyclic operation, which shows great electrochemical performance. This work indicates that smart structured electrode has great mechanical long life and electrochemical performance in battery operation. The developed analytical model may help for the electrode design and provide a theoretical way to understand the chemo-mechanical performance of the battery.